Spatio-temporal clustering analysis, temporal trends, and inequality in oral and oropharyngeal cancer mortality in Brazil over 44 years (1980–2023) - da Silva, José Mário Nunes; Menezes, Fabrício Dos Santos; Mendonça e Silva, Diego Rodrigues; da Silva, Tarsila Guimarães Vieira; Kowalski, Luiz Paulo (Spatial and spatio-temporal epidemiology, 2025)
•Oral cancer (OC) mortality decrease over time, especially among men, those aged 40–59, and in the South and Southeast regions.•Oropharyngeal cancer (OPC) mortality increased in both sexes, particularly among older adults and in the North, Northeast, and Central-West regions.•High-mortality clusters expanded over time into Brazil’s Northeast and Central-West regions.•Low-HDI areas showed the sharpest increases in mortality trends for OC and OPC. This study analyzed the temporal trends, spatial and spatio-temporal patterns of OC and OPC mortality in Brazil between 1980 and 2023, and explored their association with socioeconomic inequality. We conducted an ecological study using age- and sex-standardized mortality rates, smoothed via a local empirical Bayesian method. We assessed temporal trends through joinpoint regression. We evaluated global and local spatial autocorrelation and detected spatio-temporal clusters using a retrospective space–time scan statistic based on a Poisson model. We observed a decrease in OC mortality, particularly among men aged 40–59 years in the Southeast and South regions. In contrast, OPC mortality increased throughout the study period in both sexes, especially among individuals aged 60–79 years, with the largest increases occurring in the North, Northeast, and Central-West regions. Moran’s I revealed significant spatial dependence for both cancers. Spatial analyses identified persistent high-risk clusters in the Southeast and South, which expanded toward the Northeast and Central-West. Spatio-temporal analysis showed a recent shift of major OC clusters from the Southeast and South towards the Northeast, whereas OPC clusters continued to expand into the Central-West. Municipalities within clusters characterized by a low Human Development Index exhibited comparatively stronger increases in mortality trends for both cancers. These results underscore the need for more equitable and regionally tailored public policies to strengthen cancer control efforts in Brazil. [Display omitted]